The perceived impact of the performance management system utilised in the Department of Social Development in enhancing service delivery : a case study of the Johannesburg Metro Region. - Phungwayo, Msizi (My University, 2014)
The mandate of the Department of Social Development (DSD) is to provide welfare services. These services are targeted at every citizen in South Africa and most importantly the vulnerable and poor people of South Africa. In order to ensure that it fulfills its mandate, the Department of Social Development (DSD) has put in place a Performance Management System which seeks to ensure that the deliverables are achieved effectively and efficiently. It is often argued that services for the poor are sometimes poor services, yet government devotes ample resources to improve these services. Thus the implementation of Performance Management System is strategically geared at improving service delivery in government departments. The Department of Social Development (DSD) is one of those departments that have implemented the Performance Management System but the results reveal that it has not achieved the expected outcomes, There is heightened job dissatisfaction, poor performance and low morale. The study sought to investigate the perceived impact of the performance management system on service delivery. The primary aim of the study was to investigate the contributions of the performance management system of the Department of Social Development (DSD) in enhancing the delivery of social services. The study employed a qualitative approach and it was exploratory in nature. The study population consisted of social workers and managers. In addition, there were key informants drawn from the Human Resource section. A total of 15 participants and 2 key informants were selected using purposive sampling. Semi-structured interview schedules were used to collect data. There were separate interview schedules for social workers as well as the managers. Face to face interviews were conducted with all the participants. The collected data was analysed using thematic content analysis. Ethical considerations were adhered to, as the researcher observed and adhered to conducting the investigation without bringing harm to participants and allowing the participants free will to choose to participate in the study. The major findings revealed that there is no common understanding of what performance management is. The study revealed that the performance management system utilised in the DSD had a negative impact on service delivery. All the participants identified the performance management system as a management tool. Various challenges that undermine the effectiveness of the performance management system were identified. These challenges include the role of supervision was identified as being suppressed as proper supervision did not take place and political interference was also identified as a challenge that undermined the effectiveness of system. The work output of social workers was affected by these various challenges.
Keywords: Performance management systems; Social services; Service delivery; Social development; DSD